The monetary transmission mechanism at the euro-area level: issues and results using structural macroeconomic models - Peter McAdam; Julian Morgan (European Central Bank (ECB), 2001)
This paper addresses some of the issues faced by macroeconomic model builders in analysing the monetary transmission mechanism. These include the sensitivity of the policy simulation results to changes in the monetary and fiscal policy rule and the introduction of forward-looking behaviour in the model. To illustrate the importance of these issues the paper reports the results of variant monetary policy simulations at the euro-area level using the AWM and NiGEM models
Keywords: C50; C52; E5; 330; euro area; macro models; monetary transmission mechanism